2015
DOI: 10.18553/jmcp.2015.21.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacists’ Views on Biosimilar Naming Conventions

Abstract: BACKGROUND: As the date for the introduction of biosimilars in the United States approaches, questions remain regarding the naming, coding, and approval process for these agents that will need to be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 2 publications
2
19
0
Order By: Relevance
“…New and shorter target substems were adopted in 2009 [39]. They generally consist of a consonant, plus a vowel which is omitted if the source substem begins with a vowel.…”
Section: Naming Of Monoclonal Antibodies and Biosimilarsmentioning
confidence: 99%
“…New and shorter target substems were adopted in 2009 [39]. They generally consist of a consonant, plus a vowel which is omitted if the source substem begins with a vowel.…”
Section: Naming Of Monoclonal Antibodies and Biosimilarsmentioning
confidence: 99%
“…A fourth option is to use the branded name of the drug. A fifth option is to use the same INN once comparability and interchangeability have been demonstrated [28].…”
Section: Global Biosimilar Naming Conventionsmentioning
confidence: 99%
“…use of the same INN for biosimilars, suggest that any other naming convention may result in less automatic substitution for interchangeable biologics [28]. Owens et al [29] demonstrated that more than 76 % of prescribers assume that drugs with the same INN are structurally identical.…”
Section: Global Biosimilar Naming Conventionsmentioning
confidence: 99%
See 2 more Smart Citations